History of Pediatric Dentistry in Nepal - Birajee, Gajendra; Koirala, Bandana; Limbu, Senchhema; Dali, Mamta; Shrestha, Sneha (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Pediatric dentistry is an age-defined specialty that includes a vast array of oral healthcare-related disciplines for children. It is the most needed health care services and yet the most neglected in Nepal. Specialist pediatric dental practice in Nepal started around two decades ago. The Nepalese Association of Pediatric Dentistry (NAPD) is a nonprofit, non-government, national organization of pediatric dentists of Nepal formed with the motto of uplifting oral health of children throughout the country. NAPD is consistently conducting conferences, workshops, continuing dental education (CDE) programs and symposiums. It also serves community by conducting many free oral health check-ups, and oral health awareness rallies for fulfilling the purpose of maintaining the good oral health of children.